Female Doctors: Myths and Facts - Bilal Bin Younis (Shalamar Medical & Dental College, Lahore, Pakistan, 2019)
More than 70 percent of medical students in Pakistan are women. However, this does not translate into the working doctors' gender ratio. There are reasons behind female doctors not able to work in medical field. These reasons need to be addressed. These are the very real and practical issues women doctors are faced with. These include extensive duty hours, lack of private rooms for breastfeeding, day-care facilities and child-friendly environment for doctors who are mothers. As for women doctors who are married and without children, extensive duty hours as well as rude and sometimes hostile behavior of patients remain very pertinent issues. We should reform policies to suit the schedule of female doctors. Reforms should be begun to accommodate female doctors.